Finite element analysis of a lateral microelectro-thermal actuator - Azira, Abd Aziz; Abdul Rahman, Mohd. Saad, Prof. Madya; Hasnizah, Aris (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/